AN ANALYSIS OF RHETORICAL MOVES AND TRANSLATION TECHNIQUES IN ABSTRACTS ACROSS DEGREES - Fanny Kurniawati Putri, - (2021)
Many students consider an abstract as a difficult section because it contains essential information from a scientific paper. This study aims to investigate and compare rhetorical moves and translation techniques of students' abstracts in Indonesian and English across degrees. Sixty Indonesian and English-translated version abstracts written by social science undergraduate, graduate, and postgraduate students were analyzed using Hyland's (2000) and Molina and Albir's (2002) framework. This study found that there are differences in the realization of Move in Indonesian and English abstracts. This may be due to the frequent use of a literal translation technique. This study concludes that differences in degrees of education may affect the move and step realization. Moreover, a more effective technique of translation should be employed to preserve the equal meanings conveyed in the abstracts. It is recommended for universities to provide an abstract template for students.